Mosquito larval habitats and public health implications in Abeokuta, Ogun State, Nigeria - Adeleke, MA; Mafiana, CF; Idowu, AB; Adekunle, MF; Sam-Wabo, SO (Tanzania Journal of Health Research, 2008)
The larval habitats of mosquitoes were investigated in Abeokuta, Nigeria in order to determine the breeding sites of the existing mosquito fauna and its possible public health implications on the residents of the City. The habitats were sampled between August 2005 and July 2006 using plastic dippers and a pipette. The habitats were grouped asground pools/ponds, gutters/open drains, tyres, domestic containers and treeholes/ leaf axils. Ten species of mosquitoes were encountered in the five habitats namely Mansonia africana, M. uniformis, Culex quinquefasciatus, Aedes aegypti, Ae. albopictus, Ae. vittatus, Cx tigripes, Anopheles gambiae s.l., An. funestus and Eretmapodite clnysogaster. Ae. aegypti bred in all the habitats sampled while Cx quinquefasciatus bred in four habitats except tree holes/leaf axils. An. gambiae s.l and Ae. albopictus occurred in three habitats while other species bred only in one or two habitats. Ground pools and domestic containers recorded the highest number of species followed by gutters/open drains. Tree holes/leaf axils was the least preferred habitat with the lowest number of species occurrence. However, statistical analysis revealed non-signifi - cant difference in species occurrence in the fi ve habitats. The availability of the habitats to support the breeding of Aedes, Culex and Anopheles, which are known vectors of urban yellow fever, lymphatic fi lariasis and malaria suggest that the residents of Abeokuta City are at risk of mosquito-borne diseases. It is important that residents of the City are enlighten on the environmental factors that contribute to mosquito breeding and that the Government should institute proper sanitation measures to reduce mosquito breeding sites. Keywords: mosquito vectors, larval habitats, Nigeria Tanzania Journal of Health Research Vol. 10 (2) 2008: pp. 103-107